2021
DOI: 10.7759/cureus.12951
|View full text |Cite
|
Sign up to set email alerts
|

External Ventricular Drainage in Patients With Acute Aneurysmal Subarachnoid Hemorrhage After Microsurgical Clipping: Our 2006-2018 Experience and a Literature Review

Abstract: ConclusionEVD ensures effective monitoring and reduction of ICP. EVD is associated with a relatively low risk of infectious, liquorodynamic, and hemorrhagic complications and does not worsen outcomes when used in patients with aSAH. We propose that all patients in the acute stage of SAH with H-H severity of III-V should receive EVD immediately before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…EVDs are frequently placed in patients with aSAH, yet optimal EVD management is a subject of debate, and currently there are no definitive guidelines. Studies have shown that aSAH patients in whom EVDs are placed seem to improve clinically in the short-term; however, the association between EVD use and long-term outcomes remains unclear [ 3 , 11 13 ]. EVD placement in SAH patients seems to be associated with improved long-term outcomes in some studies, [ 13 , 14 ] and presence of hydrocephalus was associated with decreased hospital mortality in another study (likely due to prompt treatment with EVDs) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EVDs are frequently placed in patients with aSAH, yet optimal EVD management is a subject of debate, and currently there are no definitive guidelines. Studies have shown that aSAH patients in whom EVDs are placed seem to improve clinically in the short-term; however, the association between EVD use and long-term outcomes remains unclear [ 3 , 11 13 ]. EVD placement in SAH patients seems to be associated with improved long-term outcomes in some studies, [ 13 , 14 ] and presence of hydrocephalus was associated with decreased hospital mortality in another study (likely due to prompt treatment with EVDs) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in management, aneurysmal subarachnoid hemorrhage (aSAH) continues to be associated with high morbidity and mortality [ 1 ]. A substantial proportion (recent case series suggest 22–74% [ 2 , 3 ]) of aSAH patients undergo cerebrospinal fluid diversion via an external ventricular drain (EVD). An EVD can be lifesaving—for example in the management of hydrocephalus and elevated intracranial pressure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 For patients with EVD, necessary to maintain adequate intracranial pressure or having a CSF shunt, the external persistence exists, making the meningitis difficult to cure. 27 The incidence of EVD infection ranges from 2 to 22%, 28 The best way to reduce infection risk is to remove the EVD as soon as it is no longer needed, thereby decreasing the duration of catheterization which is the most significant risk factor for ventriculitis. 29 The patient needs assisted breathing in the state of PNM, which means that the health of a patient is more serious, and that is one of the risk factors for death.…”
Section: Discussionmentioning
confidence: 99%